2020
DOI: 10.1039/d0dt00541j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and electrochemical and magnetic studies of M(hfac)2 (M = CuII, CoII) and Nd(hfac)3 complexes of 4-amino-TEMPO

Abstract: Five 4-amino-TEMPO–M(hfac)n (M = CuII, CoII, NdIII) complexes with unprecedented structures are reported, together with their electrochemical and magnetic properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Systems with low spin density on the coordinating atoms of the radical ligand lead to weak magnetic exchange, particularly when used in conjunction with the contracted 4f-orbitals of the paramagnetic lanthanide ions. The presence of weak magnetic exchange coupling in multinuclear complexes typically engenders the type of SMM properties coined by fast magnetic relaxation and no magnetic memory, rendering them less suitable for applications such as high-density data storage. One strategy to enhance the magnitude of the magnetic exchange coupling is to implement highly electron-withdrawing ancillary ligands such as hexafluoroacetylacetonates, as shown in radical-containing complexes, which are proposed to augment the Lewis acidity of the metal ion. , Excitingly, this suggests that the ancillary ligand scaffold is capable of influencing the interaction between the metal center and the spin density of the bridging ligand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems with low spin density on the coordinating atoms of the radical ligand lead to weak magnetic exchange, particularly when used in conjunction with the contracted 4f-orbitals of the paramagnetic lanthanide ions. The presence of weak magnetic exchange coupling in multinuclear complexes typically engenders the type of SMM properties coined by fast magnetic relaxation and no magnetic memory, rendering them less suitable for applications such as high-density data storage. One strategy to enhance the magnitude of the magnetic exchange coupling is to implement highly electron-withdrawing ancillary ligands such as hexafluoroacetylacetonates, as shown in radical-containing complexes, which are proposed to augment the Lewis acidity of the metal ion. , Excitingly, this suggests that the ancillary ligand scaffold is capable of influencing the interaction between the metal center and the spin density of the bridging ligand.…”
Section: Introductionmentioning
confidence: 99%
“… 26 29 One strategy to enhance the magnitude of the magnetic exchange coupling is to implement highly electron-withdrawing ancillary ligands such as hexafluoroacetylacetonates, as shown in radical-containing complexes, which are proposed to augment the Lewis acidity of the metal ion. 7 , 30 Excitingly, this suggests that the ancillary ligand scaffold is capable of influencing the interaction between the metal center and the spin density of the bridging ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Moreover, a large number of studies showed that postsynthetic functionalization or direct syntheses with ligands having suitable functionality can impart hydrogen bond capabilities to the organic-inorganic hybrid. 24,25 Besides, one of the most widely studied functional groups that have been used to impart hydrogen bonding capabilities to the hybrid is the amino, carbonyl, anhydride, cyano group, etc., [26][27][28][29][30] Even more recently, the self-assembly processes are sensitive to diverse synthetic conditions in some cases, change of reaction conditions such as the solvent, pH and temperature for a given set of organic ligands and metal ions can cause various supramolecular architectures. 31,32 In this regard, solvent molecules or counter-ions (CH3COO -, NO3, NO2, ClO4 -, etc) may also dramatically influence the overall solid-state architecture Please do not adjust margins Please do not adjust margins by participating in metal coordination and hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%